BRYOZOANS OF THE GENERA STOMATOPORA BRONN AND STOPORATOMA GEN. NOV. (STENOLAEMATA) FROM THE MIDDLE JURASSIC OF MOSCOW CITY AND THE MOSCOW REGION - Viskova L.A. (My University, 2006)
Encrusting uniserial bryozoans are recorded from the Middle Callovian of Moscow city and the Moscow Region: Stoporatoma gerasimovi gen. et sp. nov. and three species of the genera Stomatopora Bronn; i.e., S. dichotoma (Lamouroux), S. waltoni Haime, and S. bajocensis (Orbigny). Some morphological characters and environmental conditions of these bryozoans are discussed. A new bryozoan that is characterized by a large size and distinctive circular reptozooecia is described.
Keywords: Callovian; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский